Broadband electrically tunable VO2‑Metamaterial terahertz switch with suppressed reflection. Issue 8 (10th March 2020) - Schalch, Jacob S.; Chi, Yaojia; He, Yulian; Tang, Yahua; Zhao, Xiaoguang; Zhang, Xin; Wen, Qiye; Averitt, Richard D.
Abstract: Devices designed to dynamically control the transmission, reflection, and absorption of terahertz (THz) radiation are essential for the development of a broad range of THz technologies. A viable approach utilizes materials which undergo an insulator‐to‐metal transition (IMT), switching from transmissive to reflective upon becoming metallic. However, for many applications, it is undesirable to have spurious reflections that can scatter incident light and induce noise to the system. We present an electrically actuated, broadband THz switch which transitions from a transparent state with low reflectivity, to an absorptive state for which both the reflectivity and transmission are strongly suppressed. Our device consists of a patterned high‐resistivity silicon metamaterial layer that provides broadband reflection suppression by matching the impedance of free space. This is integrated with a VO2 ground plane, which undergoes an IMT by means of a DC bias applied to an interdigitated electrode. THz time domain spectroscopy measurements reveal an active bandwidth of 700 GHz with suppressed reflection and more than 90% transmission amplitude modulation with a low insertion loss. We utilize finite‐difference time domain (FDTD) simulations in order to examine the loss mechanisms of the device, as well as the sensitivity to polarization and incident angle. This device validates a general approach toward suppressing unwanted reflections in THz modulators and switches which can be easily adapted to a broad array of applications through straightforward modifications of the structural parameters.